1993
DOI: 10.1136/jcp.46.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Use of proliferation cell nuclear antigen immunoreactivity for distinguishing hydropic abortions from partial hydatidiform moles.

Abstract: Aims: To determine whether the expression of proliferating cell nuclear antigen (PCNA) in villous cytotrophoblast could distinguish between placental tissue from a hydropic abortion and that from a partial hydatidiform mole. Methods: Tissue from 18 partial hydatidiform moles, 15 hydropic abortions, five normal first trimester placentas and five normal full term placentas were immunostained for expression of PCNA, using the monoclonal antibody PC10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…,atients There was a significant difference between nd the the Ki67 indexes of the first trimester and ic inditerm placentas. This supports the previous findings that there was very active growth of ion of the trophoblast in the first trimester placentas, ns has and such villous trophoblast growth is much gists in diminished in term placenta.23 27 Thus Ki67 ly used expression seems to have a logical correlation 7 Ki67. with the proliferative activity in normal plaprotein centas.…”
Section: Resultssupporting
confidence: 87%
“…,atients There was a significant difference between nd the the Ki67 indexes of the first trimester and ic inditerm placentas. This supports the previous findings that there was very active growth of ion of the trophoblast in the first trimester placentas, ns has and such villous trophoblast growth is much gists in diminished in term placenta.23 27 Thus Ki67 ly used expression seems to have a logical correlation 7 Ki67. with the proliferative activity in normal plaprotein centas.…”
Section: Resultssupporting
confidence: 87%
“…Previous studies investigating the proliferation rate of trophoblast, especially those using PCNA immunostaining, have generated considerable controversy. Suresh et al ., 7 Jeffers et al ., 24 Schammel and Bocklage 3 and our team 5 reported that the PCNA index had limited use in differentiating molar and non‐molar trophoblast or CM from PM and could not be applied as a reliable marker for predicting the outcome of HM. In contrast, Ostrzega et al ., 4 Ozbilim et al 27 .…”
Section: Discussionmentioning
confidence: 93%
“…Quantitative assessment of immunoreactivity for proliferating cell nuclear antigen (PCNA) and Ki67 antigen (MIB1) is the most frequently used method for the study of cell proliferation in cancer. Most previous reports on these two markers suggest that Ki67 is useful and may be better than PCNA in the differential diagnosis of GTD 3–8 . Staining for PCNA can be associated with technical challenges and is limited to fixed, paraffin‐embedded tissues 9 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been attempts to differentiate between complete mole (CM), partial mole (PM) and hydropic abortion (HA) using morphological 1 , morphometric 2 and proliferative indices 3 . In each instance authors fail to appreciate that villous size, appearance and proliferative activity of trophoblast vary as pregnancy advances and no corrections are made for gestational age 4 .…”
Section: Introductionmentioning
confidence: 99%